Distribution patterns and coexistence of neurohormonal peptides (ANP, BNP, NPY, SP, CGRP, enkephalins) in chromaffin cells and nerve fibers of the anuran adrenal organ - Reinecke, Manfred; Heym, Christine; Forssmann, Wolf-Georg (Cell & tissue research, 1992)
Immunohistochemical techniques were used to study the adrenal organs of the anuran species Rana esculenta, Caldula pulchra and Bufo marinus with respect to the distribution and coexistence of atrial natriuretic peptide (ANP), brain natriuretic peptide (BNP), substance P (SP), calcitonin gene-related peptide (CGRP), neuropeptide Y (NPY), Leu-enkephalin (Leu-ENK). Met-enkephalin-Arg-Phe (MEAP) and dynorphin A 1-17 (DYN). Antisera against enzymes involved in catecholamine synthesis, i.e., dopamine-β-hydroxylase (DBH) and tyrosine hydroxylase (TH), were used for the identification of chromaffin cells. ANP-immunoreactive (-IR) cells occurred in high densities (30%-70% of the total cell population) in all species investigated. In C. pulchra and B. marinus, BNP-IR cells constituted a population of non-DBH-IR and non-TH-IR cells that were different from the ANP-IR cells. A large proportion of the adrenal cells (10%-55%) were immunoreactive to Leu-ENK, and a minority (2%-5%) showed MEAP-immunoreactivity. DYN-immunoreactivity was not observed. The anurans studied exhibited small numbers of SP-IR, CGRP-IR and NPY-IR cells. Immunoreactivities for ANP+Leu-ENK and Leu-ENK+ MEAP were shown to coexist. In C. pulchra and B. marinus, immunoreactions for ANP+NPY, ANP+SP and SP+CGRP were also colocalized. Except for DYN, all neurohormonal peptides also occurred in intra-adrenal nerve fibers. SP-IR fibers also displayed CGRP-immunoreactivity and some Leu-ENK-IR fibers contained MEAP-immunoreactivity. In C. pulchra, NPY-IR fibers were found that also showed ANP-immunoreactivity.
Gesehen am 10.11.2025